Terapi Thought Stopping pada Pasien Gangguan Persepsi Sensori Halusinasi: Studi Kasus - Wahyuni, Sri; Rosdiar, Rosdiar (STIKes Surya Global Yogyakarta, 2024)
Background of Study: Hallucinations are one of the symptoms of mental disorders in which patients experience changes in sensory perception, as well as feeling false sensations in the form of sound, sight, taste, touch, or smell. This research explains Thought Stopping therapy which is used to reduce signs of hallucinations. Methods: his case study uses the Psychotic Symptom Rating Scales (PYSRAT) instrument to measure signs of hallucinatory symptoms before and after Thought Stopping therapy. The number of patients who received therapy was 3 patients. Results: igns of hallucinations. This case study uses the Psychotic Symptom Rating Scales (PYSRAT) instrument to measure signs of hallucinatory symptoms before and after Thought Stopping therapy. Before therapy, the questionnaire score obtained in patient 1 was 25, patient 2 was 30, and patient 3 was 11. After being implemented for 5 consecutive days, it was found that 2 of the 3 patients experienced a decrease in the score for signs of hallucinations, namely patient 1 obtained a score of 21 and patient 2 was 25. Meanwhile, patient 3 did not experience a decrease in score due to several obstacles, namely the patient's focus. Conclusion: ased on the results of this application, thought stopping therapy can be used as additional therapy for patients with hallucinations by paying attention to the criteria for patients who will be given therapy such as cooperative patients, patients with phase 1 hallucinations, patients with good concentration and a calm environment Keywords: Case Study; Hallucination; Schizophrenia; Thought Stopping Theraphy